Features of Poetic Ecphrasis in A. Pushkin’s Poem “The Commander” (1835): from Draft to Clean Copy - I. A. Kiselyova; K. A. Potashova (Научный диалог)
The urgency of the matter is associated with the need to clarify the features of Pushkin's pictorial ecphrasis. For the first time it is indicated that the originality of the ecphrasis in the poem “The Commander” is determined by its odic genre content, characterized by plasticity, kaleidoscopicity, and spatial dimensionality. The role of lexical and grammatical semantics, semantics of syntactic constructions in the visualization of the verbal image and the verbalization of the pictorial artifact was determined by comparing the drafts and the clean copy of the poem “The Commander”. Particular attention is paid to verbs with visual and mental meaning, creating the effect of presence, the effect of visual allusions, the effect of a revived picture, creating a psychological portrait of the hero. The role of adverbs and demonstrative pronouns with deictic semantics, contributing to the creation of the effect of presence and serving as a means of designating spatial coordinates, is indicated. The role of reception of movement and reception of contrast in creating the illusion of a visually perceived image is emphasized. Through an analytical analysis of the ecphrasis of the poem "The Commander", Pushkin's concept of the image of General M. B. Barclay de Tolly, who appears as a rejected and unappreciated heroic figure by the crowd. The hypothesis is put forward that by verbalizing the portrait of the work of J. Dow, Pushkin canonizes in the mind of the reader the hero of the Patriotic War of 1812, poetically transforming his portrait into an icon.